THE FACTORS AFFECTING QUALITY OF FINANCIAL STATEMENTS IN LANGKAT REGENCY WITH THE INTEGRITY OF FINANCIAL MANAGEMENT AS MODERATING VARIABLES - Hartono, Hartono (International Journal of Public Budgeting, Accounting and Finance, 2018)
The objective of the research was to analyze the influence of human resources competence, the use of information technology, and the implementation of internal control system on the quality of financial statement of Langkat District Administrationwith the integrity  of financial managers as moderating variable. The research used  analitic survey method. The population was 52 Work Units (Regional Work unit) in Langkat District Administration. Each Work Unit was represented by Financial Administrator and an expenditure treasurer as the respondents.The samples were taken by using census  sampling technique  (total population). Hypothesis was tested by using multiple linear regression analysis with  an Statistical Package for Social Science (SPSS) software program. The result of the research showed that human resource competence, the use of information technology and the implementation of internal control system simultaneously  and partially  had positive and significat influence on the quality of financial statementof Langkat District Administration. The integrity of financial managersas moderating variable was able to moderate  the correlation of human resources competence, the use of information technology, and the implementation of internal control system  with the quality of financial statementof Langkat District Administration.